Contribution of Mycorrhizal Fungi on Growth and Salinity Resistance of Citrus Roots (Citrus, Sp) - Palupi N.P (Nabatia, 2021)
Abiotic stress conditions with high salinity cause a decrease in plant growth and production in citrus plants. The application of mycorrhizal fungi with various species is expected to be able to overcome this problem to improve plant root conditions. The results showed that the application of mycorrhizal fungi was able to improve roots so as to increase nutrient absorption, be able to maintain plant conditions under salinity stress gradually, and be able to increase the capacity of higher seedlings to control ROS formation and to activate enzymatic and non-enzymatic antioxidant defenses.